Challenges faced by the school administration while carrying out various welfare practices on secondary school teachers in Bondo sub-county, Kenya - Otieno, Kennedy O.; Ajowi, Jack O.; Bosire, Joseph N. (Mediterranean Journal of Social Sciences, 2015)
The study sought to determine the teaching staff welfare practices and their effect on work performance of secondary schools teachers in Bondo Sub-County. The study was necessitated by discrepancy in work performance out put of the teaching staff as observed in achievements in curricular and co-curricular activities in secondary schools in Bondo Sub-County. The objectives of the study were to: assess the challenges faced by the school administration while carrying out various welfare practices and establish coping strategies employed by school administration to solve the challenges faced in offering the practices. The study was based on Social Action Theory which postulates that if a worker is not satisfied with the work environment, it will affect the services the worker renders to the institution. The research design for this study was descriptive survey design. A total of 330 respondents comprising of 240 teachers, 30 principals, 30 Board of Management chairpersons and 30 Parents Teachers Association chairpersons formed the population of the study. In each school, in the 30 chosen schools in Bondo Sub-county, eight teachers – two from each of the four departments, the principal, chairpersons of Board of Management and Parents Teachers Association were chosen for the study. The study used a combination of purposive sample and simple random technique to select the respondents. In conducting the survey, document analysis, three sets of questionnaires and interview schedule were drawn up. One set was administered to the Board of Management chairperson, the principal and the other set to the teaching staff. Information from Parents Teachers Association chairperson were obtained using interview schedule only. Research experts in the Department of Curriculum and Management at Jaramogi Oginga Odinga University of Science and Technology evaluated the instruments to ascertain their content validity. A pilot study was conducted in 10 percent of the population to test the reliability of the instruments. Simple descriptive statistics in form of mean rating, pie-charts and frequency counts using Statistical Package for Social Sciences was employed to analyze the data in order to establish relationship between the variables. The study was significant to educational practitioners and stakeholders and challenged them to adopt staff welfare practices that purely motivate the teaching staff hence enhancing their efficiency and effectiveness in discharging their duties. The study found out that welfare practices affect performance and productivity of teachers. From the findings, there emerged the need for welfare practices that purely motivate the teaching staff. The following were recommended for further research; government financial support & its effect on school management and scheme of promotion & its effect on teacher’s performance.
DOI: 10.5901/mjss.2015.v6n2p479
Keywords: Teaching Staff; Welfare Practices and Work Performance